2010
DOI: 10.1002/art.27445
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of CCN2/Connective tissue growth factor expression in the nucleus pulposus of the intervertebral disc: Role of Smad and activator protein 1 signaling

Abstract: Objective. To investigate transforming growth factor ␤ (TGF␤) regulation of connective tissue growth factor (CTGF) expression in cells of the nucleus pulposus of rats, mice, and humans.Methods. Real-time reverse transcriptionpolymerase chain reaction and Western blot analyses were used to measure CTGF expression in the nucleus pulposus. Transfections were used to measure the effects of Smads 2, 3, and 7 and activator protein 1 (AP-1) on TGF␤-mediated CTGF promoter activity.Results. CTGF expression was lower in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
81
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 59 publications
(89 citation statements)
references
References 38 publications
8
81
0
Order By: Relevance
“…Given that Smad3 and Smad4 form a complex in the nucleus even in the absence of TGF- 39,40) , it is likely that Runx2 acts as corepressor of the Smad3/Smad4 complex to inhibit basal activity of the CTGF promoter under basal conditions. Consistent with this assumption, previous studies showed that CTGF expression is reduced in cells derived from Smad3-null mice 41,42) , suggesting that the Smad3/Smad4 complex supports basal CTGF gene expression and is subjected to Runx2-mediated repression, irrespective of TGF- …”
Section: Runx2 Inhibits Endogenous Ctgf Gene Expression In Vsmcssupporting
confidence: 57%
“…Given that Smad3 and Smad4 form a complex in the nucleus even in the absence of TGF- 39,40) , it is likely that Runx2 acts as corepressor of the Smad3/Smad4 complex to inhibit basal activity of the CTGF promoter under basal conditions. Consistent with this assumption, previous studies showed that CTGF expression is reduced in cells derived from Smad3-null mice 41,42) , suggesting that the Smad3/Smad4 complex supports basal CTGF gene expression and is subjected to Runx2-mediated repression, irrespective of TGF- …”
Section: Runx2 Inhibits Endogenous Ctgf Gene Expression In Vsmcssupporting
confidence: 57%
“…Further evidence of altered expression came from our own studies that showed a trend of increasing expression of ␤1, ␣5, and ␣V integrin subunits in severely degenerated human disc samples (grade 4 and 5) compared with moderately degenerated discs (grade 2 and 3). These trends failed to reach statistical significance because of large patient to patient variations as observed in previous studies of human disc tissues (3,11). Nonetheless, a strong positive correlation was observed between the expressions of these integrin subunits.…”
Section: Discussionmentioning
confidence: 60%
“…Le Maitre et al (47) showed that mechanotransduction through ␣5␤1 integrin was impaired in degenerate human NP cells, whereas Xia and Zhu (48) found that the fibronectin fragments that accumulate in the degenerative disc cause an increase in MMP-9 and -13 through ␣5␤1. Moreover, it is important to note that along with altered integrin expression and function, CCN2 levels are also elevated during disc degeneration (11,22). These findings beg the questions: Is CCN2 able to exert anti-catabolic effects in degenerate state?…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations